Speaking Skills Strategies (Arabic and English Speeches) In Extracurricular Programs of Boarding Qur’an / إستراتيجية مهارة الكلام (الخطابة العربية و الخطابة الإنجليزية) في البرنامج اللآمنهجي بمعهد تحفيظ القرآن - Masithoh, Isninda Nur (UIN Raden Mas Said Surakarta, 2021)
The objectives of this research are to describe a Comparison of the process of implementing Strategies speaking skills (delivering Arabic and English speeches) in the extracurricular program that include objectives, material, methods, and assessments in junior high school of boarding Qur'an Daarul Fath. This research uses qualitative type. Located at junior high school of boarding Qur'an Daarul Fath in January 2020-June 2020. The Subject in this study is a speech adviser. For the collection of data by way of observation, interview, and documentation. And to test the reliability of the data using the triangulation of the source. Then it was analyzed by interactive model: data collection, data presentation, and conclusion. The result of the comparison of the implementation of delivering Arabic speech and English speech which includes (1) the purpose of the implementation of Arabic and English speech is to improve students speaking skills and develop there, (2) Material used in Arabic speech from text compiled by students and in English speech from text taken from books, (3) Arabic speech method with memorization method and English speech with memorization and reading method, (4) The assessment of Arabic and English speeches using observation method, (5) The influence of Arabic speakers in improving speaking skills include influencing students to use Arabic in conversation, expand vocabularies, develop students writing skills through freewriting, the influence of English speech influence students to use English in conversation and get used to it.